Beyond a war of words? Assessing tensions on the Korean peninsula - J. Kallio; C. Salonius-Pasternak; B. Gaens; V. Sinkkonen (The Finnish Institute of International Affairs, 2022)
An exchange of bellicose rhetoric between North Korea and the US has caused serious global concerns about a possible military conflict. The methodical advances of the North Korean leadership, the limitations of the US’s actual policy options, and China’s meagre leverage are key determinants in shaping further developments.